Faktor Resiliensi Keluarga yang Merawat Anggota Keluarga dengan Skizofrenia - Iklima Iklima; Syarifah Rauzatul Jannah; Hermansyah Hermansyah; Suryane Sulistiana Susanti; Mudatsir Mudatsir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the resilience factors of families who care for family members with schizophrenia. The research method used a cross-sectional design with a total sample of 114 families of clients with schizophrenia. The data were analyzed using the chi-square test statistic and logistic regression using the stepwise method. The results showed that 51.8% of families had high resilience. The p-value obtained for emotion regulation, impulse control and self-efficacy is 0.0001, while optimism is 0.021. As for the causal analysis, the p-value = 0.851, empathy is 0.574 and achievement is 0.851. In conclusion, self-efficacy is the most dominant predictor associated with the family resilience of schizophrenic clients. Keywords: Family, Resilience, Schizophrenia